A Novel Algorithm for Denoising Image with Deep Neural Network and Spatial Filters - et. al., Mohammad Aamir Almas, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
When the image is transmitted noise is added during transmission and reception process due to various factor Like thermal noise in antennas or faulty devices, intentionally and interference of other signals. Gaussian noise is prominent among the noises and can be removed. Different methods are available for Denoising. Nowadays Deep neural network along with different algorithms are used which gives satisfactory result. One of the algorithms is proposed in this paper which uses iterative median, low pass-high boost technique along with deep neural network to do the Denoising of a noisy image.